Some corrections of the significance level in meta-analysis - Annette Böckenhoff; Joachim Hartung (Universität Dortmund, Sonderforschungsbereich 475 - Komplexitätsreduktion in Multivariaten Datenstrukturen, 1998)
In many applications we obtain test statistics by combining estimates from different experiments or studies. The usual combined estimator of the overall effect in independent studies leads to systematic overestimates of the significance level, see Li et al. (1994). This results in a great number of unjustified significant evidences. By examination of the convexity of composed functions involved and application of higher and inverse moments of the chi-square distribution we propose corrections for the estimated standard deviation of the overall effect estimator. Analytical results and simulations show that we improve the estimated significance level in such models. – – In vielen Bereichen werden Teststatistiken dadurch erhalten, da Schätzer aus verschiedenen Experimenten oder Studien kombiniert werden. Der üblicherweise verwendete Schätzer des Gesamteffektes aus unabhängigen Studien führt zu systematischen Überschätzungen des Signifikanzniveaus, vgl. Li et al. (1994), und daher zu vielen ungerechtfertigten Signifikanzen. Mit Hilfe der Konvexität zusammengesetzter Funktionen und Anwendung höherer sowie inverser Momente der x 2-Verteilung stellen wir Korrekturen für die geschätzte Standardabweichung des Gesamteffektschätzers vor. Analytische Ergebnisse und Simulationen zeigen, dass das nominelle Niveau durch diese Korrekturen besser eingehalten wird.
Keywords: 519; meta-analysis; significance level; combined estimator